The role of reference-dependent preferences in the idiosyncratic volatility puzzle: Evidence from Korea - Le Thi Minh Hang; Hoang Van Hai; Nguyen Truong Son (Cogent Economics & Finance, 2020)
In this paper, the role of the reference-dependent preference in the relationship between idiosyncratic volatility and future return was investigated in the Korean stock market from July 1990 to June 2018. The capital gains overhang was used as a reference point for a definition of the loss and gains domain. As a consequence, the negative idiosyncratic volatility-return relationship is driven by unrealized capital losses. In addition, this negative relation disappears in the unrealized capital gains domain, suggesting the important role of the reference-dependent preference in the idiosyncratic volatility puzzle interpretation. These findings are robust to control for several factors, such as market beta, return reversal variable, momentum, and liquidity.
Keywords: G10; G11; G40; G41; 330; capital gains overhang; expected idiosyncratic risk; idiosyncratic volatility; Korean stock market; reference-dependent preferences